Research, Science Identity, and Intent to Pursue a Science Career: A BUILD Intervention Evaluation at CSULB - Hector V. Ramos; Kim-Phuong L. Vu (MDPI AG, 2024)
This paper presents an analysis of survey data to examine the association between participating in one of the National Institute of Health's (NIH) funded Building Infrastructure Leading to Diversity Initiative (BUILD) program and students' intent to pursue a career in science. Data were collected from students at California State University Long Beach (CSULB) to examine the effectiveness of the BUILD Scholars program. Both BUILD Scholars and non-BUILD students were surveyed. Propensity score matching was used to generate the non-BUILD comparison group. Multinomial logistic regression results revealed that students participating in the BUILD intervention were associated with significantly higher intent to pursue a career in science. Results also showed the importance of variables such as science identity and research participation when assessing interest in science careers. These findings have implications for STEM program evaluation and practice in higher education.